Principals’ Leadership Needs for Effective Management of Secondary Schools in Meme and Fako Divisions of Cameroon - Lyonga, Ngemunang Agnes Ngale (International Journal of Education Policy and Leadership, 2022)
The purpose of this study was to assess principals’ leadership needs for the effective management of secondary schools in Meme and Fako Divisions in Cameroon by examining their professional, instructional, and communication skills. The study population consisted of 175 teachers, 31 department heads, 26 unit heads, and 16 principals from 12 schools. The findings revealed that continuous professional training and retraining, instructional supervision, effective communication, and creating a conducive environment for teaching and learning were vital to principals’ effective management of schools. Based on these findings, provisions should be made for the continuous professional training and retraining of principals; principals should frequently carry out instructional supervision and also make use of vertical and horizontal communication to clearly communicate school goals.